AN ANALYSIS OF AMBIGUITY OF ONE DIRECTION’S SONG LYRICS IN THE MIDNIGHT MEMORIES ALBUM - Diana Rozelin; Norra Erisha; Afifah Addillah Putri (English Literature Department, Adab and Humanities Faculty, 2024)
The purpose in the research to discuss about the type of ambiguity found and the meaning of ambiguity depicted in the song lyrics of One Direction’s song in the Midnight Memories album, the researcher used Stephen Ullman's theory for identify types of ambiguity and meaning of ambiguity based on Abdul Chaer's theory. This study used a qualitative descriptive analysis. The data source of this research is One Direction's song lyrics in the Midnight Memories album. Researchers analyzed all the songs contained in the album Midnight Memories. For data collection techniques, researchers used documentation techniques and data analysis techniques using techniques of data reduction, data display and conclusion. The results of this study indicate that lexical ambiguity dominates in the lyrics of One Direction song in the Midnight Memories album. Then, the contextual meaning which contains figure of speech meaning is more dominant suitable to be used as the meaning of ambiguity depicted in One Direction’s song lyrics in the Midnight Memories album.